Conservative Women in Germany and Japan: Chancellors versus Madonnas. Issue 1 (March 2020) - Gaunder, Alisa; Wiliarty, Sarah
Abstract: Despite many similarities between them, the German Christian Democratic Union (CDU) and the Japanese Liberal Democratic Party (LDP) have represented women in parliament at different rates. This article argues that differences in party organization, electoral system rules, and left party strength interact to explain the varying levels of representation of conservative women in parliament. The CDU's corporatist structure allowed it to represent diverse interests and successfully respond to challenges for female support from the left. As a result of a weaker left party challenge and a classic catch-all party organization, the LDP's attempts to incorporate women have been less extensive and largely symbolic.